Exploring the Learning Needs for Discharge Planning Among Postoperative Orthopedic Patients: A Scoping Review - Rahayu U; Ibrahim K; Herman H (Patient Preference and Adherence)
Urip Rahayu,1,2 Kusman Ibrahim,2 Herry Herman3 1Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 3Department of Orthopaedic Surgery, Universitas Padjadjaran – Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Urip Rahayu, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +62812-2020-1942, Email urip.rahayu@unpad.ac.idBackground: Postoperative orthopedic patients often experience swelling and pain, leading to fear of movement and prolonged hospital stays. These symptoms hinder daily activities and recovery. Effective discharge planning is essential to prevent complications and improve self-care, but further exploration of patients’ learning needs is needed to better tailor educational interventions.Purpose: This scoping review aimed to explore and categorize the learning needs of postoperative orthopaedic patients to optimize discharge education and transitional care.Methods: A literature search was conducted across five major databases: PubMed, Scopus, ScienceDirect, EBSCOhost, Taylor & Francis, and also search engine is Google Scholar. The keywords used were (“postoperative orthopaedic patients” OR “orthopaedic surgery patients” OR “patients after orthopaedic surgery” OR “post-surgical orthopaedic patients”) AND (“learning needs” OR “educational needs”) AND (“discharge planning” OR “hospital discharge” OR “discharge education”). Data extraction and synthesis were performed to identify key learning needs and patterns across different studies.Results: The review identified seven key learning needs among postoperative orthopaedic patients: pain management, wound care and infection prevention, complication management, mobility and rehabilitation, daily activities and quality of life, medication and health monitoring, and digital and family support. The findings highlight gaps in patient education, particularly in pain management, complication recognition, and post-discharge support.Conclusion: This scoping review highlights gaps in patient education and underscores the need for structured, comprehensive discharge planning. The reviewed literature suggests a potential link between improved patient education and better recovery outcomes, fewer complications, and greater adherence to rehabilitation programs. However, these observations are based on existing studies. Future research should include longitudinal studies on patient learning needs, healthcare provider perspectives, and the effectiveness of digital-based and personalized educational interventions tailored to specific surgical procedures.Keywords: postoperative orthopaedic patients, learning needs, discharge planning, patient education, scoping review